Microalgal biomass production through phycoremediation of fresh market wastewater and potential applications as aquaculture feeds - Mohd Apandi, Najeeha; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel; Mohd Kassim, Amir Hashim (Springer, 2019)
Microalgal biomass produced from the phycoremediation of wastewater represents an important protein source, lipids, and natural antioxidants and bioproducts. Therefore, the microalgal biomass and their derived compounds are used in animal and aquaculture feed as well as human nutrition and health products. Many microalgal species have shown promising potential for many bioproducts. However, significant processes to find the optimum quality and quantity of microalgal biomass are still required especially when it is used as a replacement for aquaculture feed. The limitations lie in the selection of microalgal species and their production. The present review discusses the potential generation of bioproducts from microalgal biomass resulting from the phycoremediation of wet market wastewater. The consortium approach in wastewater treatment and the comparison between biomass production and available common feeds for aquaculture were reviewed.